The apothecary / 1. - Meloy, Maile (The Apothecary, 2011)
Fourteen-year-old Janie Scott, newly arrived in London from Los Angeles in 1952, becomes friends with a mysterious apothecary and his son, Benjamin Burrows, and is drawn into a dangerous adventure with Benjamin when his father is kidnapped and Russian spies try to steal his book of secrets.